2018
DOI: 10.7150/jca.24057
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative lymphocyte-monocyte ratio in patients with ovarian clear cell carcinoma

Abstract: Objective: The aim of the present study was to determine the prognostic significances of markers of preoperative systemic inflammatory response (SIR) in patients with ovarian clear cell carcinoma (OCCC).Methods: A total of 109 patients diagnosed with OCCC that underwent primary cytoreductive surgery and adjuvant platinum-based chemotherapy from 2009 to 2012 were enrolled in this retrospective study. SIR markers were calculated from complete blood cell counts determined before surgery. Receiver operating charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 26 publications
5
60
0
Order By: Relevance
“…There was likewise no correlation between platinum resistance and preoperative lymphocyte count. So, PLR has nothing to do with resistance, and it is not related to survival which is consistent with most of the relevant studies [12,13,20] . Preoperative NLR level was associated with postoperative indicators such as FIGO stage, residual tumor and platinum resistance which are known prognostic factors in OCCC [5] .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There was likewise no correlation between platinum resistance and preoperative lymphocyte count. So, PLR has nothing to do with resistance, and it is not related to survival which is consistent with most of the relevant studies [12,13,20] . Preoperative NLR level was associated with postoperative indicators such as FIGO stage, residual tumor and platinum resistance which are known prognostic factors in OCCC [5] .…”
Section: Discussionsupporting
confidence: 85%
“…The plasma D-dimer level, which significantly elevates in patients with OCCC, was associated with the incidence of deep venous thrombosis [7] as well as clinical progression and poor prognosis in malignancies including ovarian cancer [8,9] . Plenty of studies have shown that elevated NLR is linked to poor prognosis among patients with solid tumors including gynecologic cancers [10,11] , and markers of systemic inflammatory response could provide useful prognostic information of overall survival in patients with OCCC [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Summary of studies examining SIR as prognostic factors in OCCC patients. Kim 2016 [19] Zhang 2017 [20] Kwon 2018 [12] Yoshida 2019 [13] The present study…”
Section: Authors' Contributionsmentioning
confidence: 87%
“…Plasma D-dimer levels, which are signi cantly elevated in patients with OCCC, are associated with the incidence of deep venous thrombosis [7] as well as clinical progression and poor prognosis in malignancies, including ovarian cancer [8,9] . Numerous studies have shown that elevated NLR is linked to poor prognosis among patients with solid tumors, including gynecologic cancers [10,11] , and markers of systemic in ammatory response could provide useful prognostic information of overall survival in patients with OCCC [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the prognosis of patients with cancers is associated with not only the characteristics of the tumor itself but also the systemic inflammatory response [2]. For instance, it is reported that a variety of routine inflammation-based prognostic scoring systems, like the NLR, PLR and lymphocyte-monocyte ratio (LMR), have prognostic significance for different tumors [3][4][5][6]. Hypercoagulability is another physiological change in cancer patients.…”
Section: Introductionmentioning
confidence: 99%